Explaining index-based livestock insurance to pastoralists - McPeak, J.G.; Chantarat, S.; Mude, Andrew G. (Emerald Publishing Limited, 2010)
Purpose – The purpose of this paper is to present the methods and findings of an experimental game designed to extend the concept of index-based livestock insurance in northern Kenya, and analyze patterns of game play. The paper is designed to inform others who may be attempting something similar to this work in other developing country agricultural settings. Design/methodology/approach – The paper presents the following: descriptive context of the issue, explanation of the game design to match the conditions in the area, details of how the authors explained the game, and regression analysis of play by participants. Findings – Games designed to reflect key elements of the local production system can be an effective way of explaining financial products to rural producers in developing countries. Research limitations/implications – It remains to be seen if the extension effort leads to more informed consumers of insurance products, which the authors hope to address in future work. Also, the approach described in this paper is very labor intensive, which could limit use in a wide ranging extension program. Social implications – The authors were able to explain the idea to groups that were mixed: female and male. It will be interesting to see if there are any gender dimensions to insurance use. In addition, with competing claims to livestock with complex property rights, there is a need to monitor how insurance interacts with social ideas of livestock ownership. Originality/value – This is a completely new idea in the area of arid and semi-arid livestock production, the challenge is pronounced, and as insurance becomes more important in the development economics toolkit, the authors believe others can benefit from seeing what they have done.